The Dimeric Peptide (KKYRYHLKPF)2K Shows Broad-Spectrum Antiviral Activity by Inhibiting Different Steps of Chikungunya and Zika Virus Infection - Ayusso, Gabriela Miranda [UNESP] (2023)
Chikungunya virus (CHIKV) and Zika virus (ZIKV) are important disease-causing agents worldwide. Currently, there are no antiviral drugs or vaccines approved to treat these viruses. However, peptides have shown great potential for new drug development. A recent study described (p-BthTX-I)2K [(KKYRYHLKPF)2K], a peptide derived from the Bothropstoxin-I toxin in the venom of the Bothrops jararacussu snake, showed antiviral activity against SARS-CoV-2. In this study, we assessed the activity of this peptide against CHIKV and ZIKV and its antiviral action in the different stages of the viral replication cycle in vitro. We observed that (p-BthTX-I)2K impaired CHIKV infection by interfering with the early steps of the viral replication cycle, reducing CHIKV entry into BHK-21 cells specifically by reducing both the attachment and internalization steps. (p-BthTX-I)2K also inhibited the ZIKV replicative cycle in Vero cells. The peptide protected the cells against ZIKV infection and decreased the levels of the viral RNA and the NS3 protein of this virus at viral post-entry steps. In conclusion, this study highlights the potential of the (p-BthTX-I)2K peptide to be a novel broad-spectrum antiviral candidate that targets different steps of the replication cycle of both CHIKV and ZIKV.